Mental health information systems in resource-challenged countries: experiences from India. (19th April 2018) - Ahuja, Shalini; Shidhaye, Rahul; Semrau, Maya; Thornicroft, Graham; Jordans, Mark
Abstract : Mental health information systems are increasingly being used to measure the effectiveness of mental health interventions. Little or no data is available for mental health service availability and service uptake in low- and middle-income countries. Through a narrative review, this paper illustrates the importance of routine monitoring data and suggests methods for developing, implementing and evaluating mental health indicators in low- and middle-income countries with a primary focus on India.